Effects of selection and local adaptation on resilience and economic suitability in Apis mellifera carnica - Kovačić, Marin; Puškadija, Zlatko; Dražić, Marica Maja; Uzunov, Aleksandar; Meixner, Marina D.; Büchler, Ralph (Springer Science and Business Media LLC, 2020)
Modern techniques of selective breeding show high potential to improve economically important traits of honey bees. However, breeding may neglect fundamental rules of natural selection. The objective of this study was to analyze the effects of selection and local adaptation on some relevant breeding traits of Apis mellifera carnica We compared open mated queens from three different origins: local Croatian genotypes that are under controlled selection since five generations (MS), a local genotype that was never under selective breeding (NS) and, finally, a non-local genotype from a long-lasting German breeding program (HS). Generally, colonies with queens from breeding programs had better scores for defensive behavior, calmness, and swarming. In contrast, colonies from the NS group showed higher expression of Varroa destructor resistance traits. Although the HS group showed the highest score in most of the behavioral traits, the low overwintering index of colonies from this group after both wintering periods indicated a lack of local adaptation. This research underlines the relevance of breeding activities for the resilience of honey bee populations and the achievement of local adaptation.
Keywords: A. m. carnica / Selective breeding / Local adaptation / Resistance / Resilience